A Study of Natural Language Processing Procedures - Muralidharan, M; Valli Mayil, V (International Journal of Computer Sciences and Engineering, 2025)
Informatics techniques, for example, content mining and natural language processing, are constantly required in bioinformatics examine. In this review, we talk about content mining and natural language processing techniques in bioinformatics from two points of view. Initially, we plan to scan for information on science, recover references utilizing content mining techniques, and reproduce databases. For instance, protein connections and quality ailment relationship can be mined from PubMed. At that point, we examine the uses of content mining and natural language processing systems in bioinformatics, including foreseeing protein structure and capacity, recognizing noncoding RNA. At last, various strategies and applications, and also their commitments to bioinformatics, are talked about for later use by content mining and natural language processing analysts.